Implementation of Group Discussion to Improve Learning Outcomes of Class X Students of SMK Indonesia Raya in Islamic Education Learning - Putriyani, Winda (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using group discussion methods. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were vocational high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the group discussion method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 44.51%, the first cycle 71.39% and in the second cycle it increased to 84.66%. Thus, the use of group discussion methods can be used as an alternative to improve student learning outcomes in Islamic religious education learning.